2012
DOI: 10.1002/gps.3879
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration, β‐amyloid and mood disorders: state of the art and future perspectives

Abstract: Given the intriguing association between change in plasma level of Aβ, depression and cognitive impairment, future work should focus on the relationship between Aβ peripheral level(s), biomarkers of neurodegeneration and development of dementia in patients affected by mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 189 publications
(221 reference statements)
0
10
0
Order By: Relevance
“…The authors suggested that depression could reflect a prodromal stage of dementia. In this scenario, a significant reduction of β-amyloid peptide and a high Aβ40/Aβ42 ratio in depressed patients have been reported and these findings increase the risk for dementia 22 . However, this result remains to be clarified since another group that aimed to analyze the impact of depression on incident dementia developed a population-based prospective study of a large cohort of the elderly and the authors found no clear association between both conditions 23 .…”
Section: Discussionmentioning
confidence: 92%
“…The authors suggested that depression could reflect a prodromal stage of dementia. In this scenario, a significant reduction of β-amyloid peptide and a high Aβ40/Aβ42 ratio in depressed patients have been reported and these findings increase the risk for dementia 22 . However, this result remains to be clarified since another group that aimed to analyze the impact of depression on incident dementia developed a population-based prospective study of a large cohort of the elderly and the authors found no clear association between both conditions 23 .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the serotoninergic system is altered in AD (Trillo et al, 2013 ; Ramirez et al, 2014 ; Verdurand and Zimmer, 2017 ), and amyloid deposition in the brain impairs the serotoninergic activity in animal models (Colaianna et al, 2010 ; Ledo et al, 2013 ). Aβ peptides display neurotoxic activity (Piccinni et al, 2013 ), and they could also alter the brain inflammatory response, which in turn modifies the expression of indoleamine2,3-dioxygenase and impairs serotoninergic transmission (Ledo et al, 2013 ; Mahgoub and Alexopoulos, 2016 ). Hence, in early stage AD, suicidal behavior could be related to alterations of serotoninergic transmission (Madsen et al, 2011 ), which have been linked to impulsive and aggressive behavior (Lai et al, 2003 ; Vermeiren et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In depression, the serum A␤ 40/42 ratio (a peripheral marker of brain AD pathology) is elevated in depressed compared with non-depressed individuals consistently across studies, even in participants aged below 40 years [177]. Studies using cerebrospinal fluid markers of A␤ 42 , arguably a more reliable measure of AD pathology, yield mixed results, showing lower, equal or greater levels in depressed versus non-depressed individuals [177].…”
Section: Annex 1: Ad Pathologymentioning
confidence: 99%